Emergency Medical Service Use Among Latinos Aged 50 and Older in California Counties, Except Los Angeles, During the Early COVID-19 Pandemic Period - Esmeralda Melgoza; Esmeralda Melgoza; Hiram Beltrán-Sánchez; Hiram Beltrán-Sánchez; Hiram Beltrán-Sánchez; Arturo Vargas Bustamante; Arturo Vargas Bustamante (Frontiers Media S.A., 2021)
The COVID-19 pandemic has disproportionately affected Latino adults aged 50 and older in California. Among adults aged 50-64, Latinos constitute approximately one-third (32%) of the population, but over half (52%) of COVID-19 cases, and more than two-thirds (64%) of COVID-related deaths as of June 2, 2021. These health disparities are also prevalent among Latinos 65 years and older who constitute 22% of the population, but 40% of confirmed COVID-19 cases and 50% of COVID-related deaths. Emergency medical services (EMS) are an essential component of the United States healthcare system and a vital sector in COVID-19 response efforts. Using data from the California Emergency Medical Services Information System (CEMSIS), this study examines racial and ethnic differences in respiratory distress related EMS calls among adults aged 50 and older in all counties except Los Angeles. This study compares the early pandemic period, January to June 2020, to the same time period in 2019. Between January and June 2019, Latinos aged 50 and older had statistically significantly lower odds of respiratory distress related EMS calls compared to Blacks, Asians, and Whites. During the early pandemic period, January to June 2020, Latinos aged 50 and older had statistically significantly lower odds of respiratory distress related EMS calls compared to Blacks but slightly higher odds compared to Whites. Differences by race/ethnicity and region were statistically significant. Understanding EMS health disparities is crucial to inform policies that create a more equitable prehospital care system for the heterogeneous population of middle aged and older adults.